2020
DOI: 10.4467/16890027ap.20.006.12674
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Tolerance and Protein Carbonylation Caused by Irradiation of Resting Cysts in the Free-living Ciliated Protist Colpoda cucullus

Abstract: The ciliate Colpoda cucullus forms resting cysts to survive unfavorable environmental stresses. In this study, we have shown that Colpoda resting cysts survived exposure to a gamma radiation dose of 4000 Gy, although vegetative cells were killed by 500 Gy. After 4000 Gy irradiation, more than 90% of resting cysts and approximately 70% of dry cysts could excyst to form vegetative cells. In both cases, the excystment gradually increased after the induction of excystment. In addition, we also showed that protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The expression of genes related to stress responses and oxidoreductase activity showed upregulation, while other metabolic processes displayed down-regulation. Our results of this study support our previous claim that resting cysts are not just resting but repairing cell damages even though they cease mitochondrial metabolic activity (56), i.e., carbonylated proteins induced by gamma irradiation have been shown to be repaired in resting cysts (37). Differential gene expression during the early stage of encystment has been shown previously in transcriptomic studies of Colpoda aspera (57) and Pseudourostyla cristata (58); these observations demonstrated the presence of an early signaling pathway for encystment as had been suggested earlier (59,60).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The expression of genes related to stress responses and oxidoreductase activity showed upregulation, while other metabolic processes displayed down-regulation. Our results of this study support our previous claim that resting cysts are not just resting but repairing cell damages even though they cease mitochondrial metabolic activity (56), i.e., carbonylated proteins induced by gamma irradiation have been shown to be repaired in resting cysts (37). Differential gene expression during the early stage of encystment has been shown previously in transcriptomic studies of Colpoda aspera (57) and Pseudourostyla cristata (58); these observations demonstrated the presence of an early signaling pathway for encystment as had been suggested earlier (59,60).…”
Section: Discussionsupporting
confidence: 91%
“…The vegetative cells were induced by En-medium with or without 0.3% NaCl. The encystment rate was calculated as described previously (37).…”
Section: Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be the reason that Geotrichum candidium cells could maintain better metabolic activity through this new strategy. It was reported that the damage of ciliate Colpoda cucullus by gamma irradiation was decreased when incubated in the cyst . Therefore, it was reasonable to speculate that G.…”
Section: Resultsmentioning
confidence: 97%
“…It was reported that the damage of ciliate Colpoda cucullus by gamma irradiation was decreased when incubated in the cyst. 31 Therefore, it was reasonable to speculate that G. candidium cells could be capable of repairing the cell damage suffered from ChCl/Lys (1:2) addition in growth duration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%